Low-Cycle Fatigue Properties of the X70 High-Frequency Electric-Resistant Welded Pipes - Peng Tian; Kai Xu; Guang-ping Lu; Gui-ying Qiao; Fu-ren Xiao (Advances in Materials Science and Engineering)
The strength, toughness, corrosion, and fatigue resistance are the main requirements for evaluating the integrity of a pipeline. In this study, the tensile strength, impact toughness, and fatigue properties of the pipe body and weld joint of an X70 high-frequency electric-resistant welded (HFW) pipe were measured and the effects of microstructure and surface defects at weld joint on properties were discussed. Results show the appearance of a weakened zone at the weld joint of the X70 HFW pipe. Nevertheless, all mechanical properties, including strength and impact energy, were superior to the specified values of the API specifications for the X70 line pipe. The reduced strength, toughness, and resistance to S-N fatigue of the weld joint caused the microstructural coarsening at the weld junction zone. However, for the specimens without surface finishing, the resistance to S-N fatigue for the weld joint was further reduced. This phenomenon was mainly attributed to the burring defects and microstructural coarsening at the heat-affected zone (HAZ). Therefore, to improve the quality of the X70 HFW pipe, refining the microstructure of weld joint and reducing the deburring defects by optimizing the postweld heat treatment (PWHT) and deburring processes should be firstly considered in the future research works.